Genome Sequences of Five Nonvirulent Listeria monocytogenes Serovar 4 Strains - Sumrall, Eric (Genome Announc, 2016)
We present the complete genome sequences of five nonpathogenic Listeria monocytogenes serovar 4 strains: WSLC 1018 (4e), 1019 (4c), 1020 (4a), 1033 (4d), and 1047 (4d). These sequences may help to uncover genes involved in the synthesis of the serovar antigens—phenotypic determinants of virulence deemed clinically relevant.